(untitled) (Journal of Oriental Studies, 2016)
This article points out the peculiarities of the expression of category of quantity in modern chinese and Russian languages. The main aim of this article is to compare linguistic expressions of category of quantity in chinese and Russian languages, to find out their peculiarities and principles. Besides this peculiarities of morphological category of noun forms, which is found to be the word changing category expressed in the system of two different word forms -singular or plural form.